A comparison between novice and elite cyclists movement stability during cycling - Winter, L.; Grimshaw, P.; Bellenger, C.; Crowther, R. (Journal of Sports Sciences, 2025)
The Lyapunov Exponent (LyE) is a non-linear technique that analyses stability, which refers to the capacity of systems to mitigate environmental perturbations. Whether elite athletes have an optimised movement stability is contentious. There has been limited research exploring the differences in movement stability using the LyE between elite and novice athletes. The purpose of this study was to compare movement stability between novice and elite male cyclists across a 4000 m bout, using the LyE. Participants completed two sessions of cycling (familiarisation and testing). Inertial measurement units were attached to the head, thorax, pelvis and left and right shanks to measure segment accelerations. The LyE was calculated using five, 100 cycle intervals across the bout. Elite cyclists had greater segment movement instability compared to novices at the head and pelvis in the longitudinal and medio-lateral direction, thorax in the medio-lateral and anterior-posterior direction and medio-lateral shanks. Both novice and elite cyclists demonstrated increased head, thorax and pelvis movement instability across the bout. This increase in instability across the bout may demonstrate the impact of fatigue on movement stability. Future research needs to now examine movement stability in the velodrome and explore the correlation between movement stability and aerodynamic drag.